Limitations on Social Media Acceptance for Women from an Islamic Legal Perspective - Abidin, Muhammad (Universitas Nurul Jadid, 2023)
Today, social media has a significant influence on the mindsets of women. Particularly for those who are presently observing the Iddah period, unlimited use of social media can cause and contravene Shari'a regulations. In Islamic law, there is a concept known as iddah, which seeks to purify the womb and prevent actions that may cause injury (damage). As those reasons, this research aimed to analyze the law regarding the use of social media by iddah-observant women. To achieve this aim, the researcher employed normative research methodologies to evaluate library literature. Relevant texts and study results are used as data for this study. The data analysis was conducted qualitatively. The research findings indicate that the legal use of social media by women can be conducted in conformance with restrictions that have no negative effect on family continuity and harmony. Alternatively, if its use results in injury, its use becomes haram.